(untitled) - Casu, Barbara (Harlow, 2015)
Offers a comprehensive insight into the business of banking, providing up-to-date information about the impact of the financial crisis upon the banking sector globally and the far-reaching regulatory reforms. Written by expert authors, this book covers both theoretical and applied issues relating to the global banking industry, highlighted by examples from across Europe and the wider international arena
Keywords: Ngân hàng,Banks and banking,Bank management,Bank management; Châu Âu,Europe,Europe,Europe